Entre competências e competências: limites e possibilidades na configuração das organizações - Cenedezi-Zanarotti, Vanessa Regina (2005)
This work analyses the emergence of Competence concept and its implications for workers management on organizations, included considering the existent discussion about the necessity of substituting the Qualification concept for the Competence one, on attempt of making a better aprehension about the complexes aspects inherent to contemporary set. For that, were realized a bibliographyc research related to the theme and a field research. Through configuration of a more dynamic set around organizations, resulting mainly of the tecnology advance process, with effect in the society evolution, emerge adaptation needs that demand reestructuration actions of administrative and productive ambit, which one influence, over all, on humans resources management. From observation of high workers rotation number that ocurred in the Volkswagen motors plant on, located in São Carlos city, interwiews were realized with the target of identifying the criterions that govern the personnel management politics practiced on this organization, the factors that contribute to the construction of carreer expectancy and analysing the professional skyline evolution demanded as a response to observed workers rotation. Several aspects inherent to Competence logic were implicitament identified on studied organizational surrounding, which ones influence on the politcs of personnel management, on construction and frustration related to carreer expectance and on aspects that compose the professional skylines demanded. Besides, it is evident that the Competence approach is actually in vigour, and too that transition through enterprise pass since its implantation, culminating on bigger stabilization of its strucutre, represents a fundamental element on expectations and oportunities generated in such surrounding.